IMPLIKASI KEPERCAYAAN DAN KEPUASAN SANTRI TERHADAP KUALITAS PELAYANAN KOPERASI PONDOK PESANTREN NURUL ULUM ORO DALAM DESA SEJATI KEC. CAMPLONG KAB. SAMPANG - Faisol; Usman; Siti Qamariyah (STIE Bakti Bangsa Pamekasan, 2022)
The Salafiyah Islamic Boarding School Nurul Ulum Orodalam was founded by the late KH. Rifai around 1955, Cooperative PP. Nurul Ulum is part of the efforts to improve the welfare of the Islamic boarding school and students. The trust and satisfaction of the students towards the quality of service of the pp cooperative. nurul ulum is a target for achieving quality in increasing future corporate profits, bearing in mind that santri are permanent consumers in PP cooperatives. Nurul Ulum, which certainly influences the existence and stability of the cooperative. The qualitative approach emphasizes the process analysis of inductive thinking processes related to the dynamics of the relationship between observed phenomena, and always uses scientific logic. Qualitative research is a research method used to reveal problems in work life. Currently, cooperatives are growing in other countries with the aim of providing welfare to their members. This is proven by the many economic problems that can be overcome by the existence of cooperatives. Among them there are several factors that can influence consumer confidence in a product in cooperatives, namely: experience, quality of work and intelligence.